Voter Apathy in Nigeria as Political Protest: A Critical Overview of People’s Participation in Elections in Nigeria - Abdullahi, Muhammad; Arabo, Umar Abubakar (Advances in Social Sciences Research Journal, 2023)
This study explained that since the return to civil rule in 1999 after decades of military interregnum, Nigeria was involved in series of elections in the country. It has been observed that in each of these elections low turnout of voters used to be recorded. Several efforts were made with a view to assuage this malaise but, the citizens’ full participations always fell below expectations. The paper uses qualitative method which involves key informant interview as well as Aristotle’s theory of politics and thus argues that, until the elected officials in Nigeria recourse to fulfilling their campaign promises, and elections superintendents live up to expectation by making the electorates votes count during elections, above all, entrenchment of good governance, the menace of voter apathy will continue to be experienced in the Nigeria’s political space.